Enzymatic production of fructooligosaccharides from phytoenzymes of ananas comosus waste by using response surface methodology: one factor - Nur Dini, M. J.; Noormazlinah, Ahmad; Norhanimah, Hamidi; Nurul Aini, Mohd Azman (Universiti Malaysia Pahang, 2018)
Fructooligosaccharides (FOS) are low calorie sweeteners with prebiotic property which is widely used as functional food material. FOS can be produced by using phytoenzymes from Ananas comosus waste. Pineapple (Ananas comosus) fruits are available at most of Asean country. In this work, One Factor at A Time (OFAT) by Response Surface Method (RSM) using Design Expert version 7.0 have been applied to optimize the FOS concentrations by enzymatic reaction of sucrose with phytoenzymes from Ananas Comosus waste. The studied variables were: temperature (30-90 ̊C), pH (3-9), time of reaction (10-120 minutes), sucrose concentrations (20%-80%w/v) and phytoenzymes concentrations (10%-100%w/v) of reaction correspondingly. As a result, an optimum condition FOS production was obtained are, time of reaction (100 minutes), temperature (60 ̊C), pH (5.5), sucrose concentration (60%w/v), and phytoenzymes concentration (30% w/v), respectively and producing 150.456 (g/ml).This investigation can be further extended to explore the prebiotic potential of synthesized FOS.